Development Of A Learning Module Using The Self Organized Learning Environment (Sole) Model With Augmented Reality Assistance On The Materials Of Rotation Dynamics And Equality Of Rigid Bodies - Oktaviyani Rosniadi Pratama; Connie Connie; Eko Risdianto (IJOEM: Indonesian Journal of E-learning and Multimedia, 2022)
This research aims to describe the characteristics of the learning module by using the Self Organized Learning Environment (SOLE) model with the aid of Augmented Reality on the material of rotational dynamics and rigid body equilibrium, to describe the feasibility of the learning module using the Self Organized Learning Environment (SOLE) model with the aid of Augmented Reality on the dynamics material rotation and equilibrium of rigid bodies and describe students' perceptions of the readability of learning modules using the Augmented Reality-assisted Self Organized Learning Environment (SOLE) model on the material of rotational dynamics and rigid body equilibrium. This research method is a Research and Development (R&D) method with a 4D development method modified into 3D, namely define, design and development. The resulting product is a printed learning module using the Self Organized Learning Environment (SOLE) learning model assisted by Augmented Reality video playback made using the Unity 3D application. This module aims to train high school students critical thinking skills. The data samples used in this study were physics teachers and class XI students from three schools. The instruments used in this study were observation sheets, review sheets of learning implementation plan documents, the teacher needs questionnaires, student needs questionnaires, expert team validation questionnaires, and student perceptions questionnaires. Assessment of the validation test questionnaire and students' perceptions were interpreted with a Likert scale. Product validation was carried out by 3 expert validators who were reviewed from 6 aspects, namely content, presentation, critical thinking indicators, language, SOLE model stages, and media. The results obtained from this study indicate that the developed module is included in the very decent category with an average score percentage of 85.96% and students' perceptions of the developed module are in the very good category with an average score percentage of 90.01%.